(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
The semantic web is a vision which captures information from the web and makes it possible to help machines to understand complex human requests. Such intelligence based understanding requires important sources of information to be structured semantically so that the meaningful information can be accessed and provided to the users. The main outcome of the current idea is to derive the development of search engines to provide the users with artificial intelligence experience. The achievement of this idea requires integration of autonomous tools and standards. The technology can be realized to its task potentially by incorporating/deploying intelligent agents in semantic web.